Reconstructing Other Property Rights: Comparative Analysis of Divergent Interpretations in Indonesian Civil Code and Ministerial Ship Registration Regulations - Aulia Rifai; Amaliyah; Marwah; Fauzia P. Bakti; Lukmansyah Rifai; Padma Liman (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to analyze the comparison between other concepts of property rights regulated in the Indonesian Civil Code and the regulations in the Minister of Transportation Regulation on Ship Registration and Nationality. The problem arises because both of these concepts grant rights of control and utilization over a vessel, yet they are not included in the definition of property rights as regulated in Book II of the Indonesian Civil Code. The research method used is normative juridical with a statutory and conceptual approach. Legal materials were analyzed by interpreting the provisions of the Indonesian Civil Code and the Minister of Transportation Regulation and by testing their application through the practice of ship registration. The results of the study show that bareboat charter and leasing in maritime transport law have characteristics similar to property rights, especially in the aspects of publicity through registration and legal certainty for third parties. However, conceptually, both are still positioned as personal rights within the Indonesian Civil Code. The novelty of this research lies in the finding that special regulations in the field of maritime transport law indirectly develop the construction of other property rights outside the framework of the Indonesian Civil Code, thereby encouraging a reinterpretation of the boundaries between property rights and personal rights in the context of Indonesian maritime transport law.